Original Digital Color Image Reconstruction Using Smooth Hue Transition Estimation Method - Rao B, Prabhakar; Prasad, Shraddha; kumar , B.P.Pradeep (International Journal of Psychosocial Rehabilitation, 2020)
The reconstruction of digital color image nearer to its originality using non-adaptive estimation methods will produce zipper-effects or artifacts in general. But though the smooth hue transition color estimation method is also non-adaptive, it overcomes the problem of the artifacts and reconstructs the original image in a better way. The color estimation methods are mathematically analyzed and implemented using Matrix Laboratory tool for the digital image is not an image for an engineer but a matrix of numbers from zero through two hundred and fifty-five. As a result of implementation, images and Minimum Mean Square Errors and Signal to Noise Ratios are obtained. The performance evaluation of the algorithms under consideration is done with their help. These digital color image reconstruction methods are widely used for commercial, educational and entertainment, machine and robotic vision applications. These are cost-effective color image reconstruction methods due to the usage of single chip charge couple device for capturing primary colors of the original scene.